Initial assessment of radar reflectivity-rainfall rate, Z-R relationships for moderate rain events in Malaysia - Sobli, Nuurul Hudaa; Ismail, Ahmad Fadzil; Mohd. Isa, Farah Nadia; Mansor, Hasmah (IEEE Xplore, 2013)
and rainfall rate (R), identified as Z-R relationships have been derived to facilitate the rainfall rate estimation by weather radar. Most of the previously proposed Z-R relationships were implied as too generalized and only applicable within the region that has identical climate characteristics or behavior. Based on such notion, the most accurate Z-R relationship applicable for Malaysian weather radar therefore needs to be investigated and identified. In this paper, two renowned models will be evaluated on how well they fit to Malaysian weather radar data. Preliminary comparisons between the previously proposed Z-R relationships using newly acquired radar data in Malaysia and ground-based rain gauge measurements are also presented. The use of inaccurate relationship can cause error in radar rainfall estimates. This might pose unacceptable risk for the aviation industry where accurate, dependable weather information deduced by radar system is expected at all times.